Mechanisms Underlying the Production Effect for Singing - Quinlan, Chelsea K.; Taylor, Tracy L. (Canadian journal of experimental psychology, 2019)
The production effect is defined as better memory for items that were read aloud compared with items that were read silently. Quinlan and Taylor (2013) expanded the findings of the production effect by demonstrating that singing items produces even better recognition performance than reading aloud, and argued that this was due to enhanced relative distinctiveness. The current study tested three alternative accounts. In Experiment 1, we explored whether singing results in a larger production effect because it is deemed more bizarre than reading aloud. To address this, we tested a sample for whom singing does not seem bizarre: experienced singers. They also showed better recognition of items that were sung compared with those that were read aloud. In Experiment 2, we determined that singing appears to take longer than either reading aloud or reading silently; however, the possible effect of production time was further explored in Experiment 3. We did this by instructing participants to sing quickly, read aloud slowly, or read silently. Altering relative production times resulted in no discernible changes in subsequent recognition performance. Finally, in Experiment 4, we explored whether singing might strengthen the memory trace relative to reading aloud. We tested this by manipulating the production instruction between subjects. This eliminated the recognition advantage for both reading items aloud as well as for singing them aloud. Having ruled out these alternatives, we argue that singing improves subsequent recognition because it offers more distinctive elements than either reading aloud or reading silently. L'« effet production » correspond à l'amélioration des performances mnémoniques des sujets qui doivent lire des éléments à voix haute plutôt qu'en silence. Quinlan et Taylor (2013) ont poussé plus loin les conclusions relatives à l'effet production en démontrant que le fait de « chanter » les éléments se révélait encore plus productif que la lecture à voix haute, soutenant que ceci était dû à un accroissement du caractère distinctif relatif. Trois explications possibles été mises à l'essai dans le cadre de l'étude. Lors de l'expérience no 1, nous avons exploré la possibilité que l'effet production plus marqué était dû au fait que chanter les éléments est jugé plus « hors de l'ordinaire » que la lecture à voix haute. Pour vérifier ceci, nous avons contrôlé un échantillon de sujets pour qui le chant est une activité tout à fait ordinaire : les chanteurs expérimentés. Ces sujets ont aussi démontré une meilleure reconnaissance des éléments chantés par rapport aux éléments lus à voix haute. Dans le cadre de l'expérience no 2, nous avons déterminé que le chant semble exiger plus de temps que la lecture à voix haute ou la lecture silencieuse. Cependant, c'est dans le cadre de l'expérience no 3 que la durée possible de l'effet production a été explorée un peu plus en détail. Pour ce faire, nous avons demandé aux participants de chanter rapidement, de lire à voix haute lentement ou de lire silencieusement. La variation du temps de production relatif n'a eu aucun changement visible sur la performance de reconnaissance subséquente. Enfin, dans l'expérience no 4, nous avons exploré la possibilité que le fait de chanter puisse renforcer la trace mnésique relative à la lecture à voix haute. Nous avons testé ceci en manipulant les instructions de production parmi les sujets. Ceci a permis d'éliminer l'avantage de la lecture à voix haute et du chant des éléments en vue de leur reconnaissance. Ayant écarté ces explications possibles, nous soutenons que le chant améliore la reconnaissance subséquente, car il offre plus d'éléments distinctifs que la lecture à voix haute ou la lecture silencieuse. Public Significance Statement Compared with when words are read silently at study, subsequent recognition is better if those words are read aloud, and best if they are sung. We rule out other alternative explanations to suggest that singing is a particularly effective memory strategy because the words become relatively distinct.